Historiopreneur dan Potensi Budaya Melayu dalam Pemajuan Industri Pelancongan (Parawisata): Pengalaman Malaysia - Zaid Ahmad; Mohd Samsuddin (Proceeding International Conference on Malay Identity, 2022)
Abstract: This paper aims to examine several aspects related to historiopreneur, entrepreneurship, history, and heritage - making historical elements a commercial commodity that has commercial value. It includes culture which is part of history. All of that is summarized as a commodity for the development of the historical tourism industry. History and culture is something that is very synonymous with a civilization. Meanwhile, a civilization is characterized by its identity by its cultural history and heritage. In Malaysia, historical tourism has existed for a long time. However, the existence of historical tourism at this time is arguably still sideways to various other tourism sub-sectors such as entertainment, sports and recreation, nature, beaches, medicine and food. Studies and observations show that there are still many locations, artifacts and remains of historical value in this country that have not been given a proper place to be used as tourism products. This paper will look at the current scenario of tourism products based on history and culture in Malaysia. Challenges and potential as well as future steps in advancing the tourism sub-sector based on history and culture will also be discussed. Keywords: historiopreneur, travel, history, culture, heritage